KLASIFIKASI KARAKTERISTIK BUSANA TRADISIONAL CHINA - Kisni Hangganingtyas; Dhea Putri Aguatina S,A; Amin Sulistiyowati (Akademi Seni dan Desain Indonesia Surakarta, 2024)
The Online Journal of Akademi Seni dan Desain Indonesia Surakarta comprises of 13 online journals which contribute to the advance of knowledge in 13 scientific fields. To comply to the formatting used by the Journal, authors who wish to submit paper to one of the Journal are strongly recommended to use this file as the template for their papers. In this file, authors will find all styles and formatting acceptable for paper submission. Each paper should be between 8 to 12 pages in all, including illustrations, tables, list of references, and abstracts in Bahasa Indonesia and English. Authors are encouraged to submit paper in MS Word format (.doc or .docx) via http://jurnalonline.itenas.ac.id as registered author. Hardcopy is acceptable for first submission, but softcopy is required for further editing once the paper is considered for publication by the Journal. Keywords: author’s guideline, document’s template, format, style